Answer:
p(x) = (2x +1)(x +3)(x -4)
Explanation:
You want to rewrite p(x) = 2x^3 -x^2 -25x -12 as a product of linear factors, given that (x+3) is a known factor.
Quadratic factor
Using synthetic division to divide p(x) by the known factor we find the factorization to be ...
p(x) = (x +3)(2x² -7x -4)
Linear factors
The quadratic is factored by looking for factors of (2·(-4) = -8) that have a sum of -7. Those factors are -8 and +1. This gives the factorization of p(x) as ...
p(x) = (x +3)(2x +1)(2x -8)/2 . . . . . where 2 is the leading coefficient
p(x) = (x +3)(2x +1)(x -4)